Simulasi Kunci Elektronis dengan Menggunakan Barcode dan Visual Basic 6.0 untuk Aplikasi Keamanan Rumah - Joko Purnomo; Wika Purbasari; Atika Ratna Dewi; Rianti Yunita Kisworini; Muhammad Akbar Setiawan (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2017)
The use of manual key circulating on the market are already not very secure anymore, because manual key has some shortcomings, among others, the key is impractical because it is too heavy to be easily lost, easily stolen and easily copied. Because of the shortage of manual key usage then increasingly unpopular people and return the switch to the use of the key that works in electronic doors. Electronic door key advantages compared with manual key lock that is not easily lost because only with memorized password, operation easier and more smooth, the key could not be stolen.The same as the programming language Basic, Pascal, C and others – other. But the Basic, Pascal and C is intended for operating systems MS-DOS, while Visual Basic is intended for the Windows operating system. The barcode is essentially the order of black and white vertical stripes with different thicknesses, very simple but very useful, with uses to store data-specific data e.g. production code, expiry date, number of identity with easy and cheap, though such technology continues to evolve with the discovery of magnetic media, electronics, Rfid tags, serial eeprom (as in smart cards), slots, scanner, to the CCD and even we can make it your own. Types of barcode is very much a traditional start from i.e.